Validation of a liquid chromatography method (HPLC-UV/Vis) to quantify aldehydes in rainwater and air - Araya Araya, Melissa; Sibaja Brenes, José Pablo; Soto Fallas, Roy; Mora-Barrantes, José Carlos; Alfaro Solís, Rosa; Borbón-Alpízar, Henry; Valdés González, Juan (Uniciencia, 2024)
Aldehydes are compounds in the atmosphere formed by the photochemical degradation of other organic compounds in the troposphere and can be emitted by natural or anthropogenic sources. [Objective] An analytical method was implemented to quantify aldehyde samples in matrices such as air and rainwater. [Methodology] Aldehyde sampling and analysis were conducted using method TO-11 from the United States Environmental Protection Agency (EPA). Sampling was carried out by using adsorption cartridges coated with a 2,4-DNPH solution, forming a hydrazone with the aldehydes present in the rainwater and the air, which were tested using a liquid chromatograph coupled to a UV-visible detector (HPLC-UV/Vis). To validate the analysis technique and the analytical quality of the results, the following was determined: linearity, sensitivity, quantification limits, detection limits, repeatability, reproducibility, and recovery percentage. In the case of repeatability, the comparison of the Horwitz coefficient of variation was used with the percentages of relative standard deviation (% RSD) of the samples. [Results] The detection and quantification limits obtained range between 0.18 μg/m3 and 3.20 μg/m3 for acetaldehyde and acrolein, respectively, while quantification limits are between 0.62 μg/m3 for acetaldehyde and 4.70 μg/m3 for heptanal, data that characterizes the method’s analytical quality. [Conclusions] In general, the analysis method for aldehydes showed linearity, with R2 values equal to or greater than 0.9991 for each calibration curve, and relative deviation percentage values less than 2.25 %, indicating good precision in the analysis.